Assessing the Suitability of Fifth Grade Textbooks on 'Ecosystems and Our Environment' in Lebong Elementary Schools - Guntur Gunawan; Andri Aprillia; Yosi Yulizah; Yuyun Yumiarty (AL-ISHLAH: Jurnal Pendidikan, 2024)
This descriptive-quantitative study examines the eligibility of Grade 5 student textbooks on the theme of ecosystems and the environment at Lebong Regency Elementary School, using survey and observation to collect data and analyze it quantitatively. Lebong District's 93 elementary schools, including 180 fifth-grade teachers, are sampled using regional sampling, a random selection technique taken per sub-district. The study's main data is gathered through a questionnaire and secondary data from sources like textbooks for class IV students on the theme of "Ekosistem dan Lingkungan Sahabat Kita". The results of the research show that the conformity factor of material description with KI and KD is considered quite appropriate with an average percentage of 56.76%. Then, in terms of accuracy, the material was assessed as meeting the requirements with a percentage of 62.92%. Then, in terms of learning support materials, it was also assessed as meeting the requirements with a percentage figure of 64.3%. Finally, Factors for suitability of material descriptions with KI and KD, material accuracy factors, and learning support material factors were also declared to meet the requirements after obtaining a percentage figure of 62.47%. The results of the research concluded that the feasibility of a textbook for fifth-grade students on the theme of ecosystems and the environment of Our Friends at Lebong Regency Elementary School was eligible because it met several criteria such as the suitability of the material with Core Competencies (KI) and Basic Competencies (KD), material accuracy, learning support material, suitability of material descriptions with KI and KD, material accuracy factors and learning support material factors. The study reveals positive aspects of Lebong Regency Elementary School's Grade 5 student textbooks on ecosystems, including conformity with Core Competencies, accuracy, and learning support. However, improvements include aligning with curriculum guidelines, improving content clarity, optimizing learning support materials, and continuous evaluation for better educational impact.